Como se escolhe um candidato? uma etnografia das estratégias pré-eleitorais para as eleições de 2016 - Santos, Caroline Mendes dos (Universidade Federal de São Carlos, 2018)
This research is based in the analysis of anthropology of politcs and, through fieldr research, I was able to produce an ethnography of the formation of alliances around the choices of candidates for the 2016 municipal elections in a small municipality in the state of São Paulo. The data were obtained from the monitoring of one of the political groups formed in the municipality for those elections. Thus, this ethnography is a result of the analysis of the choices for candidates, based on a series of social attributes that legitimize the choice of some to the detriment of other pre-candidates. In addition to legal issues, I observed the importance of political inheritance and political capital, relations of kinship and friendship and belonging to certain political groups, the fact of being known and having a life course considered exemplary are also fundamental for those who aim the politics of votes. Therefore, I present what would be these attributes of the pre-candidatures to the executive and municipal legislature, and the close relation with the pre-candidatures of the executive and the state legislature.
How do you choose a candidate? an ethnography of the pre-election strategies for the 2016 elections
Keywords: Antropologia da política; Pré-candidatos; Família; Grupo político; Partidos políticos; Anthropology of politics; Pre-candidates; Family; Political group; Political parties; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA; CIENCIAS HUMANAS::ANTROPOLOGIA